Influence of Low-Temperature Modes of Winter Rye Seed Storage on Its Yield-Related Traits - Zadorozhna, Olha; Yehorov, Dmytro (Problems of Cryobiology and Cryomedicine, 2022)
The effect of different storage modes for the seeds of winter rye breeidng sample (Secale cereale L. subsp. cereale var. vulgare Koern) on its longevity, germination and yield structure was studied. Seed samples with a moisture content of 5–7% were stored in an airtight container for up to 42 months at 4 and –20°C. Control of plant germination and assessment of yield-related traits were carried out for three years according to standard methods. The research findings demonstrated the variation of seed germination depending on the sample genotype. No differences were noted in the longevity of seeds after 30 and 42 months of storage under various temperature regimens. The results of the analysis of yield-related traits of plants for two or three consecutive years did not show any significant advantages when influenced by 4 or –20°C on the spike length, number of productive stems and the mass of grain derived from the spike. However, at the same time, differences were found for plant height and weight of 1,000 grains in some cases in the seeds stored at temperatures of 4 or −20°C. Probl Cryobiol Cryomed 2022; 32(2):111–120